Plant apomixis is rare in Himalayan high-alpine flora - Viktorie Brožová (Nature Portfolio, 2019)
Abstract Gametophytic apomixis is a way of asexual plant reproduction by seeds. It should be advantageous under stressful high altitude or latitude environment where short growing seasons, low temperatures, low pollinator activity or unstable weather may hamper sexual reproduction. However, this hypothesis remains largely untested. Here, we assess the reproductive mode in 257 species belonging to 45 families from the world’s broadest alpine belt (2800–6150 m) in NW Himalayas using flow cytometric seed screen. We found only 12 apomictic species, including several members of Poaceae (Festuca, Poa and Stipa), Rosaceae (Potentilla) and Ranunculaceae (Halerpestes, Ranunculus), which are families typical for high apomict frequency. However, several apomictic species were newly discovered, including the first known apomictic species from the family Biebersteiniaceae (Biebersteinia odora), and first apomicts from the genera Stipa (Stipa splendens) and Halerpestes (Halerpestes lancifolia). Apomicts showed no preference for higher elevations, even in these extreme Himalayan alpine habitats. Additional trait-based analyses revealed that apomicts differed from sexuals in comprising more rhizomatous graminoids and forbs, higher soil moisture demands, sharing the syndrome of dominant species with broad geographical and elevation ranges typical for the late-successional habitats. Apomicts differ from non-apomicts in greater ability of clonal propagation and preference for wetter, more productive habitats.